Depression and Internet use in a Sample of Malaysian Undergraduate Students - Xi, Lu (Journal of Education and Vocational Research, 2013)
This study used a set of questionnaire to investigate the Internet use and depression level in a sample of Malaysian undergraduate students, which identified 12 cases as pathological Internet use (PIU) in a total sample of 90 students using Beard and Wolf’s (2001) criterion. Students with PIU spent significantly longer time on Internet and experienced extremely higher level of depression (M=42.83, SD=11.86) than their non-PIU counterparts (M=26.26, SD=14.79), which is in the severe level. The gender difference on depression was also detected in this study but not for time spent online. Lastly, this study found that students with PIU would like to spent more time on SNS, browsing with no specific purpose, and online media viewing, while students with increasing level of depression would accelerate the time spent online, especially on SNS, browsing with no specific purpose, and instant messaging. The same Internet application (SNS and browsing with no specific purpose) chose by students with PIU and high level of depression implied that there may be close association on developing depression and PIU related to usage of SNS and browsing with no specific purpose.